O Turismo como um tema de pesquisa: um diálogo epistemológico a partir das produções dos programas de pós-graduação stricto sensu da Universidade Federal do Rio Grande do Norte, no período de 2007 a 2011 - Gouveia, Zwyla Alice Cabral (2012)
The study consists in an analysis of researches with tourism issues, in Master s and Doctoral level, investigating their epistemological trends, regarding the type of study that is being produced and the methods used. It is characterized as exploratory, documental and bibliographical, having undertaken a cross-sectional study which covers the period from 2007 to 2011. It analyzes the context of academically production in tourism, the nature of these researches, the methodological aspects adopted in these theses and dissertations, the philosophical inclinations and the coherence and contribution of the same. This research uses, the Digital Library of Theses and Dissertations (BDTD) and the secretariats of the Academic Centers of the Federal University of Rio Grande do Norte (UFRN) as means to collect data. It employs the technique of sampling by judgment and undertakes the research in various Academic Centers in UFRN, using the method of content analysis. It shows that, from the 643 studies analyzed, 43 of them have themes related to tourism, which characterized this study sample. This study realizes that PPGA is the largest producer of researches on tourism issues, ahead of PPGTur, which ranks the third position, in this aspect. Also realizes that all surveys analyzed are crosssectional and the theme further investigated, with 21% of the sample, is related to the marketing aspects of tourism, with the theme Directors of Hotels and Restaurants (DHR) . This research demonstrates that all sample surveys make use of interviews, and these are, mostly, structured. Also realizes that most of these studies, with 21% of the sample, employ the method of content analysis. The references in Portuguese are surveyed about five times more than the ones in other languages. It estimates that more than half of the sample is characterized as positivist, associated with aspects of functionalism. A minority of 21% of these researches seeks to identify and recommend solutions to the tourism issues, or even represent part of them. This research concludes that the studies in tourism are mostly unifocal, being driven by issues related to the touristic trade. PPGTur produces a number still unrepresentative of studies. The theses and dissertations of the sample are limited and/or unable to analyze the changes of the phenomenon caused by the time. The studies from the sample present criteria and make use of other methods and techniques to associate with the interviews and content analysis to obtain more solid and reliable data and results. They use a low number of references in languages other than Portuguese. Most of these studies, characterized as positivist-functionalist, investigate the functioning, planning, coordination and expectations in organizations, leaving aside other issues, also relevant for tourism. The number of studies aimed at identifying solutions to the problems of tourism, or that even represents part of them, is not expressive